Correction to: PTEN-L is a novel protein phosphatase for ubiquitin dephosphorylation to inhibit PINK1–Parkin-mediated mitophagy (Cell Research, (2018), 10.1038/s41422-018-0056-0) - Wang L. (Nature Publishing Group, 2018)
10.1038/s41422-018-0068-9